CTA organizes seminar on agricultural information sources in hispanophone countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Part of CTA's mission is to break down language barriers which can all too often hinder the dessimination of scientific and technical information. However, the seminar which CTA recently organized on agricultural information sources in hispanophone...